Pengaruh Peran Konsultan pada Performa Proyek Jalan di Kabupaten Dharmasraya - Albar, Yuda E. D.; Yulius, Nursyaifi; Anif, Bahrul (Jurnal Civronlit Unbari, 2024)
In the development of road infrastructure development, many are still found to be less than optimal in its implementation, not on time, and contract termination. One of them is road improvement work in Dharmasraya Regency. This study aims to identify the role of consultants in the performance of road projects in Dharmasraya Regency and to assess the most dominant role of consultants that influence the success of a road construction project. This research was conducted using a quantitative method. The data source uses primary data obtained from interviews and secondary data obtained from literature reviews. The research population was 81 respondents consisting of the owner, namely the Dharmasraya Regency PU Service, supervisory consultants, and implementing contractors involved in road construction and improvement projects in Dharmasraya Regency for the 2020 to 2022 budget years. The research sample used was the entire population. Data analysis techniques used factor analysis and multiple regression analysis. The results of the study found 61 sub-factors or variables that were the role of consultants in the successful implementation of road construction projects in Dharmasraya Regency. The dominant factor that is the role of consultants in controlling the implementation of road supervision in Dharmasraya Regency is the task factor with the sub-factor of coordinating all construction supervision personnel for each implementation of field measurements or engineering. The factors that are the role of consultants in controlling the implementation of road supervision in Dharmasraya Regency greatly influence costs, quality, and time with levels of influence reaching 48.3%; 56.8%; and 55.7% respectively.